Developing a halal compliance framework: The case of food manufacturing and processing - Husna, Hashim (GBMR, 2025)
Purpose: The Halal industry is one of the fastest-growing global markets, driving food companies to improve their production processes to meet Halal standards. These companies are subject to monitoring and regulation by relevant Halal authorities, whether private or public. This study aims to develop a Halal compliance framework grounded in the economic theory of deterrence. Design/methodology/approach: The literature in food economics shows that the likelihood of food risks resulting from malpractice or non-compliance increases with the potential profits from opportunistic behaviour. Although halal industry is highly regulated and routinely inspected, little is known about compliance behaviour amongst food producers. This study proposes a Halal compliance framework based on the fundamental theories of crime deterrent, legitimacy, morality and market forces. Findings: An econometric model was developed based on the proposed framework. Research limitations/implications: This framework can be used to explore Halal compliance behaviour in food processing and manufacturing firms, as well as to examine the effectiveness of the regulatory control in place. Practical implications: This model can be used to identify which of the regulatory, morality and market-based factors most significantly influence Halal compliance attitudes in food processing and manufacturing. Based on these insights, targeted incentives can be designed and implemented to effectively promote and reinforce compliance within the industry.